The Role of the Teacher In Managing Child Emotions At American Academy Casablanca School Morocco - Nurhusni Kamil; Haseena Sultan (JOYCED: Journal of Early Childhood Education, 2022)
Emotions are the most basic thing in a person. Emotional management needs to be done early on, especially for anyone so that emotions can be controlled in a better direction. In early childhood emotions need to be managed even when starting to enter school age. Many impacts will occur if a child is not able to manage his emotions properly. Emotions generated by children can be caused by many factors such as external and internal factors. The method used in this research is qualitative with a case study approach. In this study the teacher who will be the object of this research is 1 teacher. The criteria are teachers who teach early childhood aged 4-5 years who are included in group B. The purpose of this research is to see the teacher's role in managing children's emotions at the American Academy Casablanca in Morocco. Data collection techniques using interviews and questionnaires. The results of the study show that there is a teacher's role in managing children's emotions during play activities in learning activities in the classroom. There are several ways and methods that are applied by the teacher so that children are able to control their emotions in a better direction, such as the teacher will give advice to children when children are angry or sad. The next step is the teacher will use the ttime-out method if the first step cannot make the child control his emotions with the teacher's expectations.